Guest Editorial: AI-Driven Theory, Technology and Application for Sensing, Interaction, and Digitalization in the 6G Era - Chen, Min; Gharavi, Hamid; Humar, Iztok; Song, Jeungeun; Leung, Victor C. M. (IEEE wireless communications, 2023)
In the upcoming 6G era, network communication will no longer be focused solely on indicators, such as bandwidth and latency. The influx of distributed service nodes and gradually perfected deep learning theories are now pushing the network communication environment into a wave of intelligence. In the 6G era, more emphasis will be placed on the immersive experience of humans in the space where perception, transmission, and computing are integrated. Consequently, this promotes a paradigm shift from traditional sensing devices by enabling non-perceptual devices with the capability of data perception. On the other hand, it also requires researchers to realize the mining and utilization of massive data. In addition, digital twin technology has also gradually merged into traditional application fields and expanded to a wider field of enabling intelligent network services.